Basin edge effect on industrial structures damage pattern at clayey basins - Khanbabazadeh, Hadi; Zulfikar, Abdullah C.; Yesilyurt, Ali (Techno-Press, 2020)
In this numerical study, the 2D dynamic behavior of a clayey basin and its effect on damage pattern over basin edge are investigated. To attain this goal, a fully nonlinear time domain analysis method has been applied. Then, the fragility curves of the considered two typical industrial structures for that certain point are estimated using the acceleration time histories recorded at each surface point. The results show that the use of the damage related parameters in site effect analyses, instead of amplification curves, can yield more realistic estimation of the basin dynamic response. In a distance about 150 m from outcrop at the basin edge, the differences between fragility curves increase when increasing the distance from outcrop with respect to the reference rock site. Outside this region and towards the basin center, they tend to occur in rather single curves. Furthermore, to connect the structural damage to the basin edge effect, the earthquake demand value at different points for two typical structures was evaluated. It was seen that the probability of occurrence of damage increases over 250 m from outcrop, while the effect of the basin edge was limited to 150 m in case of the basin edge evaluation by using fragility curves.
Keywords: site effect; basin edge effect; 2D dynamic behavior; fragility curve